HPMA Copolymer Mebendazole Conjugate Allows Systemic Administration and Possesses Antitumour Activity In Vivo - Martin Studenovský; Anna Rumlerová; Jiřina Kovářová; Barbora Dvořáková; Ladislav Sivák; Libor Kostka; Daniel Berdár; Tomáš Etrych; Marek Kovář (MDPI AG, 2022)
Mebendazole and other benzimidazole antihelmintics, such as albendazole, fenbendazole, or flubendazole, have been shown to possess antitumour activity, primarily due to their microtubule-disrupting activity. However, the extremely poor water-solubility of mebendazole and other benzimidazoles, resulting in very low bioavailability, is a serious drawback of this class of drugs. Thus, the investigation of their antitumour potential has been limited so far to administering repeated high doses given peroral (p.o.) or to using formulations, such as liposomes. Herein, we report a fully biocompatible, water-soluble, HPMA copolymer-based conjugate bearing mebendazole (P-MBZ; Mw 28-33 kDa) covalently attached through a biodegradable bond, enabling systemic administration. Such an approach not only dramatically improves mebendazole solubility but also significantly prolongs the half-life and ensures tumour accumulation via an enhanced permeation and retention (EPR) effect in vivo. This P-MBZ has remarkable cytostatic and cytotoxic activities in EL-4 T-cell lymphoma, LL2 lung carcinoma, and CT-26 colon carcinoma mouse cell lines in vitro, with corresponding IC50 values of 1.07, 1.51, and 0.814 µM, respectively. P-MBZ also demonstrated considerable antitumour activity in EL-4 tumour-bearing mice when administered intraperitoneal (i.p.), either as a single dose or using 3 intermittent doses. The combination of P-MBZ with immunotherapy based on complexes of IL-2 and anti-IL-2 mAb S4B6, potently stimulating activated and memory CD8+ T cells, as well as NK cells, further improved the therapeutic effect.